Molecular characterization and genetic diversity of Babesia bovis and Babesia bigemina of cattle in Thailand - Srionrod, Nitipon; Nooroong, Pornpiroon; Poolsawat, Napassorn; Minsakorn, Sutthida; Watthanadirek, Amaya; Junsiri, Witchuta; Sangchuai, Siriphan; Chawengkirttikul, Runglawan; Anuracpreeda, Panat (Frontiers in Cellular and Infection Microbiology, 2022)
Babesia bovis and B. bigemina are the most common tick-borne parasites that cause bovine babesiosis which effects livestock production, leading to economic losses in tropical and subtropical areas of the world. The aims of this study were to determine the molecular detection, genetic diversity and antigenicity prediction of B. bovis based on spherical body protein 2 (sbp-2) gene and B. bigemina based on rhoptry-associated protein 1a (rap-1a) gene in cattle in Thailand. By PCR assay, the molecular detection of B. bovis and B. bigemina infection revealed levels of 2.58% (4/155) and 5.80% (9/155), respectively. The phylograms showed that B. bovis sbp-2 and B. bigemina rap-1a sequences displayed 5 and 3 clades with similarity ranging between 85.53 to 100% and 98.28 to 100%, respectively, when compared within Thailand strain. Diversity analysis of sbp-2 and rap-1a sequences showed 18 and 4 haplotypes, respectively. The entropy analysis illustrated 104 and 7 polymorphic sites of sbp-2 and rap-1a nucleic acid sequences, respectively, while those of sbp-2 and rap-1a amino acid sequences showed 46 and 4 high entropy peaks, respectively. Motifs analysis exhibited the distribution and conservation among sbp-2 and rap-1a sequences. The continuous and discontinuous B-cell epitopes have also been evaluated in this work. Therefore, our findings may be used to ameliorate the understanding inputs of molecular phylogeny, genetic diversity and antigenicity of B. bovis and B. bigemina Thailand stains.